Effect of interleukin-10 and platelet-derived growth factor on expressions of matrix metalloproteinases-2 and tissue inhibitor of metalloproteinases-1 in rat fibrotic liver and cultured hepatic stellate cells - Zhang, Li-Juan (World J Gastroenterol, 2004)
AIM: To examine the expressions of matrix metalloprotein-ases-2 (MMP-2) and tissue inhibitor of metalloproteinases-1 (TIMP-1) in rat fibrotic liver and in normal rat hepatic stellate cells, and to investigate the changes in their expressions in response to treatment with interleukin-10 (IL-10) and platelet-derived growth factor (PDGF). METHODS: Rat models of CCl(4)-induced hepatic fibrosis were established and the liver tissues were sampled from the rats with or without IL-10 treatment, and also from the control rats. The expressions of MMP-2 and TIMP-1 in liver tissues were detected by S-P immunohistochemistry, and their expression intensities were evaluated in different groups. Hepatic stellate cells (HSCs) were isolated from normal rat and cultured in vitro prior to exposure to PDGF treatment or co-treatment with IL-10 and PDGF. MMP-2 and TIMP-1 levels were measured by semi-quantitative reverse transcriptional polymerase chain reaction (RT-PCR). RESULTS: CCl(4)- induced rat hepatic fibrosis models were successfully established. The positive expressions of MMP-2 and TIMP-1 increased obviously with the development of hepatic fibrosis, especially in untreated model group (84.0% and 92.0%, P < 0.01). The positive signals decreased significantly following IL-10 treatment (39.3% and 71.4%, P < 0.01 and P < 0.05) in a time-dependent manner. TIMP-1 mRNA in PDGF-treated group was significantly increased time-dependently in comparison with that of the control group, but PDGF did not obviously affect MMP-2 expression. No difference was noted in TIMP-1 and MMP-2 expressions in HSCs after IL-10 and PDGF treatment (P > 0.05). CONCLUSION: MMP-2 and TIMP-1 expressions increase in liver tissues with the development of fibrosis, which can be inhibited by exogenous IL-10 inhibitor. PDGF induces the up-regulation of TIMP-1 but not MMP-2 in the HSCs. IL-10 inhibits TIMP-1 and MMP-2 expressions in HSCs induced by PDGF.